Nawani and nukoni applications for supporting small and medium micro enterprises in Gunung Kidul district - Asih Pujiastuti; Astika Ayuningtyas; Anggraini Kusumaningrum; Adetya Dyas Saputra (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2021)
Micro, Small and Medium Enterprises (MSME) can be defined as a productive business that can be owned by individuals or business entities and has met the criteria as a micro business. UMKM is one of the spearheads of an independent economy that has great development potential, so that the existence of MSMEs can strengthen the people's economy. One area that has a lot of MSMEs is Gunungkidul Regency which is located in the Special Region of Yogyakarta. There are many obstacles in the UMKM business in Gunungkidul Regency, one of which is in marketing and product management. Support from the technological side is needed to increase the pace of the MSME economy. One form of technology support is an inventory application that can help MSMEs in managing product stocks and supporting product marketing. Applications named Nawani and Nukoni can make it easier for MSME business players in marketing products. Nawani functions to market UMKM products and perform stock management, while Nukoni functions as a catalog for MSME products. Based on the test obtained using a Likert Scale, Nawani has a score of 78.8% for the Function Test and the UI / UX Test of 69.6%, while Nukoni has a score of 85.3% for the Function Test and the UI / UX Test for 70.2%, so that both applications are running and suitable for use by both parties.